Given,
The mass of the sled and the person, m=62.5 kg
The coefficient of the kinetic friction, μ=0.190
The harness tension, T=180.o N
From Newton's second law, the net force on the sled is given by,
![F_n=ma](https://img.qammunity.org/2023/formulas/physics/high-school/oiykjh3hxachy7dodsdv92i7wunpa06r85.png)
the net force is also given by the sum of all the forces acting on it.
Thus,
![\begin{gathered} F_n=ma=T-f \\ \Rightarrow ma=T-N\mu_{} \\ =T-mg\mu \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/32a4jzb3wg6pti0k6m1og4djierk3awdpt.png)
Where f is the frictional force and g is the acceleration due to gravity.
On substituting the known values,
![\begin{gathered} 62.5a=180.0-62.5*9.8*0.190 \\ a=(180-62.5*9.8*0.190)/(62.5) \\ =1.018\text{ m/s}^2 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/7cfzw28mkwm1m3tn6xq7f9mx35aif7qn5k.png)
Thus the acceleration of the sled is 1.018 m/s²